Penerapan Cognitive Behaviour Therapy pada Pasien Kanker - Ida Ayu Made Ari Santi Tisnasari; Tuti Nuraini; Yati Afiyanti (Journal of Telenursing (JOTING), 2022)
This study aims to analyze the use of CBT in the treatment of cancer patients. The method used is a systematic review of articles obtained from the PubMed, ScienceDirect, Springerlink and Sage Journal databases. The results showed that CBT helped overcome several problems experienced by cancer patients, such as depression, anxiety, fatigue, insomnia, fear of cancer recurrence, pain, self-efficacy problems and sexual function of cancer patients. In conclusion, CBT can be applied in the treatment of cancer patients through several approaches, such as Mindfulness Therapy (MiCBT), Group CBT, Internet-based CBT (I-CBT), video-integrated CBT (VCBT-I) and commonly practiced professional CBT. Keywords: Cancer Patients, Cognitive Behavioral Therapy (CBT)